Spatial Planning in Service Delivery Towards Distributive Justice in South Africa - Magidimisha, Hangwelani Hope.; Chipungu, Lovemore; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume presents a detailed synthesis of the historical, present-day and future state of service delivery in South Africa. The generation and distribution of services in any geographical space has been and is always a source of inequality in human society. Thus, in the context of spatial planning, space is the major factor through which distributive justice and sustainable development can be achieved. To examine the continuation of spatial inequality in service delivery, the authors employed both qualitative and quantitative research methods in a multi-pronged approach, utilizing empirical data from the Vembe District in Limpopo, data from the South African Index of Multiple Deprivation, and representative attitudinal data from the South African Social Attitudes Survey. Ultimately, this study examines spatial differences in living environments with a focus on the distribution of household services and discusses strategies to achieve spatial equality.
Part I: Creating the Stage for Interrogation.-Chapter 1: Spacial Inequality - An Introduction -- Chapter 2: South Africa in a Context -- Chapter 3: Hegemonic Global Influences on Service Delivery - A Theoretical Retreat -- Chapter 4: Methodological Considerations -- Chapter 5: Resilience in Service Delivery -- Part II: The Masquerade of a "Rainbow Nation".-Chapter 6: Exploring the Changing Context of Development in South Africa -- Chapter 7: The Development Ideology of South Africa as a Rainbow Nation -- Chapter 8: Re-living Socialism in a Neo-Liberal Dispensation -- Chapter 9: "We Have a Better Story to Tell." -- Chapter 10: The Spatial Implication of Service Generation -- Chapter 11: Citizen Participation in Planning: Balancing the Equation Between Equitable Involvement and Equitable Service Distribution -- Chapter 12: Addressing Quantitative and Qualitative Aspects of Service Delivery Through Spatial Planning -- Chapter 13: Reflections on Interactive Planning Decisions.
Keywords: Sociology, Urban; Human geography; Human rights; Urban Sociology; Human Geography; Human Rights